PENGEMBANGAN PERANGKAT DAN MODEL PEMBELAJARAN BERBASIS KONSTRUKTIVIS MATAKULIAH STATISTIKA MELALUI PENDEKATAN LESSON STUDY - Setyaningsih, Nining (Universitas Muhammadiyah Surakarta, 2012)
This research aims to produce instructional design and model-based constructivist learning course of Statistics Math through lesson study in an effort to improve the quality of learning. Besides, it is also to find the effect of the use of the device and the constructivist model of learning based on student results. This study uses the approach of research and development (research & development). Results of research and development are as follows: (1) The statistical learning mathematics, covering the syllabus, lecture and Quality Plans, and Teaching materials are ready to be validated through lesson study approach, planning, implementation, reflection, and follow-up. (2) Design-based constructivist learning model includes the stages of orientation, elicitasi, restructuring ideas, the application and review. (3) Based on the findings of the trial results and the model of learning, particularly in the development of student activity indicates that the use of constructivist-based learning model can increase the activity of students, as measured by indicators of the ability to answer questions, the ability to propose ideas, and the ability to submit allegations.